An Analysis of Competency Achievement of Elementary Teacher Candidates in Micro Teaching During The Covid-19 Pandemic - Setyo Eko Atmojo; Beny Dwi Lukitoaji (Jurnal Basicedu, 2022)
This study aims to analyze the competency achievement of prospective elementary school teacher students in micro teaching during the covid-19 pandemic. Competence in micro teaching is a fundamental competence that must be mastered by prospective elementary school teacher students. This study used descriptive qualitative method. Data collection techniques using observation techniques, questionnaires and documentation. The data analysis technique was carried out descriptively. The research subjects were students of class A6 and A7, totaling 80 students. This research was conducted from February-July 2021. The results showed that 36.50% of students achieved a score of > 71 and 45.75% of students achieved a score of > 81 which were in the high category. Meanwhile, 85.20% of students have carried out these aspects well and obtained a score of > 70. This shows that through online micro teaching that is well planned and packaged, it is still able to lead students to achieve the expected competencies. The achievement of this micro teaching competency is due to the selection of the right learning media and infrastructure. The media used has a good level of convenience and flexibility so that all students can apply it well and have a good impact on the achievement of micro teaching competencies.